The role of pulmonary thromboendarterectomy in management of chronic thromboembolic pulmonary hypertension: a case report - YILDIZELİ, BEDRETTİN (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2013)
Pulmonary thromboendarterectomy (PEA) is a single treatment of choice in selected patients with chronic thromboembolic pulmonary hypertension (CTEPH). Pulmonary thromboendarterectomy may be life-saving for patients with increased pulmonary vascular resistance (PVR) and proximal segment disease of the pulmonary arteries. A 72-year-old male case had a 50-80% occlusion in pulmonary artery branches due to chronic thromboembolism. Echocardiography revealed a pulmonary artery pressure (PAP) of 110 mmHg, while right heart catheterization showed a mean PAP of 43 mmHg and PVR of 850 dyn/s/cm-5. The patient who was diagnosed with CTPEH underwent PEA. Pulmonary artery pressure was reduced to 40 mmHg at postoperative day 15. The patient died on postoperative day 22 due to a sudden cardiac arrest. Surgery is the most effective treatment approach for CTPEH cases. All risk factors should be carefully evaluated to reduce postoperative mortality. In this article, we present a case of CTEPH patient who underwent a successful PEA and died following surgery.
Keywords: Chronic thromboembolic pulmonary hypertension; pulmonary hypertension; pulmonary thromboendarterectomy; ARTERIES